THE DESIGN OF SIMPLE EXPERIMENT TO PERFORM THE CHARACTERISTIC OF WAVE - GUNARDI (NIM 20207091), GUGUN
The phenomenon about wave is continuously studied and reaseached becaused wave has special characteristic. To understand wave, we have to understand the characterictic of wave such as diffraction, interference, reflection, refraction and polarization. On interference of water wave through two slits, resulted bright and dark pattern then these sources had phasaa difference that destructive when two wave sources that had phase difference resulted bright pattern, then these two wave sources had phase that constructive. The bright and dark pattern can be noticed clearly on the screen. This final project is design in the form of simple experiment to show wave characteristic,especially diffraction, interference and reflection can be used determining unity of wave such as : wave length, frecuency, the velocity of water wave and amplitude. On the phenomenon of water wave through 2 narrow slits, we can get the connection of wave length and the amount of node has high linearity, means if many nodes performed, then the wave length become smaller. From the result of eksperiment showed that if wave frequency get higher than wave length will be shorter.